Performance and perception of haptic feedback in a laparoscopic 3D virtual reality simulator. Issue 5 (3rd September 2019) - Hagelsteen, Kristine; Johansson, Richard; Ekelund, Mikael; Bergenfelz, Anders; Anderberg, Magnus
Abstract: Background: The benefit of haptic feedback in laparoscopic virtual reality simulators (VRS) is ambiguous. A previous study found 32% faster acquisition of skills with the combination of 3 D and haptic feedback compared to 2 D only. This study aimed to validate perception and effect on performance of haptic feedback by experienced surgeons in the previously tested VRS. Material and methods: A randomized single blinded cross-over study with laparoscopists (>100 laparoscopic procedures) was conducted in a VRS with 3 D imaging. One group started with haptic feedback, and the other group without. After performing the suturing task with haptics either enabled or disabled, the groups crossed over to the opposite setting. Face validity was assessed through questionnaires. Metrics were obtained from the VRS. Results: The haptics for 'handling the needle', 'needle through tissue' and 'tying the knot' was scored as completely realistic by 3/22, 1/22 and 2/22 respectively. Comparing the metrics for maximum stretch damage between the groups revealed a significantly lower score when a group performed with haptics enabled p  = .027 (haptic first group) and p  < .001(haptic last group). Conclusion: Haptic feedback in VRS has limited fidelity according to the tested laparoscopic surgeons. In spite of this, significantly less stretch damage was caused with haptics enabled.